2019
DOI: 10.1093/mnras/stz1682
|View full text |Cite
|
Sign up to set email alerts
|

Dust spreading in debris discs: do small grains cling on to their birth environment?

Abstract: Debris discs are dusty belts of planetesimals around main-sequence stars, similar to the asteroid and Kuiper belts in our solar system. The planetesimals cannot be observed directly, yet they produce detectable dust in mutual collisions. Observing the dust, we can try to infer properties of invisible planetesimals. Here we address the question of what is the best way to measure the location of outer planetesimal belts that encompass extrasolar planetary systems. A standard method is using resolved images at mm… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 64 publications
4
7
0
Order By: Relevance
“…model. This finding is consistent with the results obtained by Pawellek et al (2019) for debris disks around late-type stars with stellar wind. At 100 μm, where smaller grains dominate the emission, the influence of the wind drag is more visible; though the birth ring is still the brightest part of the disk, especially in the model with the strongest wind, the surface brightness inside the ring is only a few times lower.…”
Section: Collisional Evolutionsupporting
confidence: 93%
See 1 more Smart Citation
“…model. This finding is consistent with the results obtained by Pawellek et al (2019) for debris disks around late-type stars with stellar wind. At 100 μm, where smaller grains dominate the emission, the influence of the wind drag is more visible; though the birth ring is still the brightest part of the disk, especially in the model with the strongest wind, the surface brightness inside the ring is only a few times lower.…”
Section: Collisional Evolutionsupporting
confidence: 93%
“…We followed the disk evolution for 24 Myr. By assuming pure astronomical silicate (Draine 2003) as dust material, we calculated the SED of the simulated disks (for details, see Pawellek et al 2019). We found that disk models with a mass of 50 Å M -which include all solids up to the maximum size of 40 km-reproduce the measured SED at wavelengths1.3 mm well, although they cannot account for the unusually shallow millimeter SED and thus substantially underestimate the observed flux at 9 mm (see Figure 2 for an example).…”
Section: Collisional Evolutionmentioning
confidence: 99%
“…Fig. 8 complements the results found in Pawellek et al (2019). That study used collisional models and showed that at high resolution the peak of the discs' surface brightness is at the same location in sub-mm and far-infrared images (and is nearly coincident with the planetesimal belt).…”
Section: Spatially Resolved Disc Radiisupporting
confidence: 85%
“…M stars have stellar winds bring corpuscular and Poynting-Robertson drag, and consequently their debris disk tail have a surface density power law index from −1.5 to −2.5 depending on the stellar mass loss rate Ṁstar (Strubbe & Chiang 2006). However, if Ring 1 is the birth ring of small particles (see Pawellek et al 2019 for exceptions), the power law index of −0.7 for its tail is outside the expected range: it is even shallower than that for quiescent stars with Ṁstar 10 Ṁ . The existence of secondary CO gas in this system might help explain the power law index for Ring 1.…”
Section: Discussionmentioning
confidence: 99%
“…Using the relationship between α out and surface density power law index Γ out in Augereau et al (1999), i.e., Γ out = α out + β where β = 1 as in Equation ( 1 We discuss the meaning of the power law index of Ring 1 tail below assuming Ring 1 is the birth ring of small particles in the system. However, we caution that with a single birth ring, stellar winds around M stars can create multiple rings in shorter wavelengths, and the location of the brightest ring deviates from that of the birth ring (e.g., Figure 5 of Pawellek et al 2019).…”
Section: Spatial Distributionmentioning
confidence: 99%